2018
DOI: 10.1038/s41591-018-0044-4
|View full text |Cite|
|
Sign up to set email alerts
|

STAT3 labels a subpopulation of reactive astrocytes required for brain metastasis

Abstract: The brain microenvironment imposes a particularly intense selective pressure on metastasis-initiating cells, but successful metastases bypass this control through mechanisms that are poorly understood. Reactive astrocytes are key components of this microenvironment that confine brain metastasis without infiltrating the lesion. Here, we describe that brain metastatic cells induce and maintain the co-option of a pro-metastatic program driven by signal transducer and activator of transcription 3 (STAT3) in a subp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
381
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(411 citation statements)
references
References 70 publications
8
381
0
2
Order By: Relevance
“…Tumor-associated astrocytes react to the GBM microenvironment with an altered phenotype, 60 and were recently shown to promote glioma growth. 32,61 We show here that astrocytes secrete TGM2 in response to radiation, which supports stemness and radiation resistance of GBM cells. Inhibition of TGM2 decreased survival of tumor cells in an ex vivo organotypic slice model of GBM, and was previously shown to increase survival in a glioma xenograft model.…”
Section: Discussionsupporting
confidence: 58%
“…Tumor-associated astrocytes react to the GBM microenvironment with an altered phenotype, 60 and were recently shown to promote glioma growth. 32,61 We show here that astrocytes secrete TGM2 in response to radiation, which supports stemness and radiation resistance of GBM cells. Inhibition of TGM2 decreased survival of tumor cells in an ex vivo organotypic slice model of GBM, and was previously shown to increase survival in a glioma xenograft model.…”
Section: Discussionsupporting
confidence: 58%
“…A recent study showed that regulatory T cells reduce astrocyte reaction (including A1 markers) after stroke, through amphiregulin, IL6, and STAT3 signaling (Ito et al, ). Alternatively, phospho‐STAT3 + reactive astrocytes found around brain metastatic cells reduce CD8 + lymphocyte recruitment and increase the number of CD74 + macrophage/microglia, which are more permissive to metastatic proliferation [(Priego et al, ), Figure r]. Proliferating, juxta‐vascular reactive astrocytes were also shown to inhibit monocyte infiltration following SWI (Frik et al, ).…”
Section: How Do Reactive Astrocytes Interact With Other Innate Immunementioning
confidence: 99%
“…The reciprocal interactions between astrocytes and metastatic tumor cells were shown to promote brain metastasis in multiple studies . Proinflammatory signaling by astrocytes was suggested to facilitate melanoma brain metastasis . However, the mechanisms that instigate astrocyte‐mediated neuroinflammation during brain metastases formation are not well characterized.…”
Section: Discussionmentioning
confidence: 99%
“…44 Proinflammatory signaling by astrocytes was suggested to facilitate melanoma brain metastasis. 18,45 However, the mechanisms that instigate astrocyte-mediated neuroinflammation during brain metastases formation are not well characterized. Here we show that melanoma-derived EVs/exosomes instigate a proinflammatory gene signature in primary astrocytes.…”
Section: Discussionmentioning
confidence: 99%